Errors On Speech Production Made By The First And The Third Semester Students Of English Education Department Of Uii In Speaking Class For Academic Year 2016/2017 - Sholihah. TS, Akhadiyatus, Prof. Dr. Endang Fauziati, M. Hum (2017)
This study describes errors on speech production made by the first and the third semester students of English Education Department of UII in speaking class for academic year 2016/2017. The aims of this research are to describe the types of errors and frequency, the dominant error, the similarities and differences, and the error sources made by the first and the third semester students. This is qualitative research study. In collecting the data, the researcher collects the audio recording, listens and makes the script from the audio recording, read the script and identifies the data, selects the data, and classifies the type of speech error. In analyzing the data, the researcher uses the theory of Clark and Clark and Dulay, Burt, and Krashen (1982), and James (1998). The result indicates that the total errors are 294 which contains of speech error 80.61%, morphological error 7.82% and syntactical errors 11.56% which is made by the first semester students and The total errors are 322 which contains of speech error 95.05%, morphological error 2.79% and syntactical errors 2.17% made by the third semester students. The dominant error of the first semester is silent pause, while filled pause is the dominant error made by the third semester students. The similarities of errors are silent pause, filled pause, repeats, unretraced false, retraced false, stutter, interjection, slip of tongue, word selection, omission of bound morpheme s-es plural, omission of -ing, and addition of -ing. The error differences made by the first and the third semester students are in the correction, switching to L1, omission of be as auxiliary verb, of omission of article, addition of be as auxiliary verb, misordering of noun phrase and misordering of modal have to. The error sources are cognitive reason and situational anxiety.